Optimal allocation of intermittent embedded generator with time-varying generation and demand and types of load considerations - Aguirre, Rodolfo A. Jr
The problem regarding sub-optimal decisions with respect to optional embedded generation (EG) allocation is investigated by simultaneously considering the type of load and the inherent time-varying characteristics of the generation and demand. The study is made on the basis of minimizing power losses and improvement in the voltage profile of the system. A combination of simplified stochastic load flow simulation and genetic algorithm is utilized in the analysis. Genetic algorithm (GA) is used to determine the optimal allocation of the EG. A simplified stochastic load flow simulation-based approach is utilized to consider the power output of photovoltaic and wind generator models and time-varying behavior of the demand. The load models considered are residential, industrial, commercial and mixed. The study was implemented in IEEE 37-bus test system. The developed methodology has the capacity of comparing different modeling approaches in optimal EG allocation. These modeling approaches include voltage-invariant load model without temporal variation, voltage-dependent load model without temporal variation, voltage-invariant load model with temporal variation and voltage-dependent load model with temporal variation. A computer tool has been developed to implement the study. The tool can simulate up to four (4) EGs with a maximum power capacity of 28 MW in an IEEE 37-bus test system. Four (4) different modeling approaches and case studies were simulated. Results considering voltage-dependent load model with temporal variation modeling approach showed that the computed power loss may differ by as much as 13% if voltage and time-invariant models are used.